THEME AND RHEME ANALYSIS IN KURIKULUM MERDEKA ENGLISH TEXTBOOK OF JUNIOR HIGH SCHOOL - Mahfud, Ali; Rusmawaty, Desy; Kalukar, Ventje Jany (Faculty of Social and Political Sciences University of Bangka Belitung, 2024)
This research is about theme and rheme analysis using Systemic Functional Linguistic approach by Halliday. The purpose of this research is to identify theme and rheme, classify the types and components of theme and rheme and also identify the thematic development. The method used in this research is qualitative method. The research data is taken from Kurikulum Merdeka textbooks of English subjects at the junior high school level. The results showed that there were three types of themes found in the data, namely topical, interpersonal, and textual themes. Topical theme appears in 55%, interpersonal theme appears in 34%, and textual theme appears in 10%. The appearance of type theme in each clause often coincides with other themes. It is very rare for one clause to have only one theme. Thematic development found in the data is multiple theme and zigzag theme. Some data bring up themes implicitly because the type of data is in the form of dialogue which often occurs word elimination